Long-term effects of maternal separation on chronic stress response suppressed by amitriptyline treatment - Cotella, Evelin Mariel (2013)
The early-life environment has many long-term effects on mammals. Maternal interaction and early stressful events may affect regulation of the HPA axis during adulthood, leading to differential glucocorticoid secretion in response to stressful situations. These adverse experiences during postnatal development may even sensitize specific neurocircuits to subsequent stressors. Later in life, the overreaction of the HPA axis to stress can constitute a risk factor for metabolic and mental diseases. As tricyclic antidepressants are known to correct glucocorticoid hypersecretion during depression, we treated maternally separated animals with amitriptyline, at a lower dose than habitually used in depression models, to prevent the response to chronic stress during adulthood. Male Wistar rats were separated from the mother for 4.5 h every day for the first 3 weeks of life. From postnatal day 50, animals were subjected to chronic variable stress during 24 d (five types of stressors at different times of day). During the stress, protocol rats were orally administered amitriptyline (5 mg/kg) daily. We observed that maternal separation caused a reduction in plasma ACTH levels (p < 0.05), but evoked hypersecretion of corticosterone (p < 0.05) when it was combined with stress in adulthood. This rise was completely prevented by antidepressant treatment with amitriptyline.